Evaluation of metacarpophalangeal joint synovitis in rheumatoid arthritis by power Doppler technique: relationship between synovial vascularization and periarticular bone mineral density - Ozgocmen, S; Kiris, A; Kocakoc, E; Ardicoglu, O; Kamanli, A (Editions Scientifiques Medicales Elsevier, 2004)
Objective. - To evaluate intra-articular vascularization and flow patterns of the metacarpophalangeal (MCP) joints in rheumatoid arthritis (RA) patients by using power Doppler technique. The relationship between the flow patterns and the regional bone mineral density (BMD) measurements of MCP joints using dual-energy X-ray absorptiometry (DXA) was also assessed. Methods. - Fifteen patients (mean age 48.5 +/- 13.8) with a disease duration of 6.8 +/- 4.9 years were included into the study. Thirty MCP joints of three healthy subjects were also assessed as controls. Clinical activity of MCP joint inflammation was classified according to a modified index for synovitis activity based on joint swelling, warmness and pain. Ultrasonography was performed using LOGIQ 7 unit by means of a 6-13 MHz linear array transducer. Gray-scale US and power Doppler sonography (PDS) examination was performed. Using spectral Doppler the quality of flow was determined and the indices of pulsatility (PI) and resistance (RI) were measured in longitudinal plane. The erosive scores of the MCP joints were determined on the plain hand radiographs using Sharp/van der Heijde method. Hand BMD, MCP BMD and the ratio of MCP BMD to whole hand BMD (rBMD) were measured using a Lunar DPX densitometer. Results. - Total 150 MCP joints of 15 patients and 30 MCP joints of three healthy controls were examined in both hands. Flow was determined in 31 joints (10 moderately active, 21 active) in eight patients whereas seven patients had no quantifiable flow in MCP joints. MCP joints of healthy controls had no quantifiable flow. Mean PI of these joints were 2.17 +/- 2.37 in moderately active and 2.12 +/- 1.93 in active MCP joints. RI was 0.76 +/- 0.12 in moderately active and 0.75 +/- 0.15 in active MCP joints. There was no significant difference in RI and PI of these active and moderately active MCP joints. There was a significant correlation between erosive scores and PI, RI of total MCP joints (r = 0.40 and r = 0.41, P < 0.05). PI and RI also negatively correlated with rBMD (r = -0.46, P < 0.01 and r = -0.36, P < 0.05, respectively). PIc was 4.07 +/- 3.26 and RIc was 0.88 +/- 0.16 in the neighboring soft tissues which were significantly higher than PI and RI of MCP joints (P < 0.001). Conclusion. - Power Doppler ultrasonography (PDUS) is a useful method demonstrating synovial vascularization and flow patterns and offers new alternatives for monitoring disease activity and measurement of therapeutic response. Flow patterns had intimate correlation with intra-articular bone and cartilage destruction. (C) 2003 Elsevier SAS. All rights reserved.
Keywords: power Doppler sonography; synovitis; vascularization; resistive index; hand bone mineral density